What factors influence cataract waiting list time?. Issue 4 (1st April 2000) - Churchill, Amanda J; Vize, Colin J; Stewart, Owen G; Backhouse, Oliver
Abstract : AIMS: To determine whether there were any specific factors that influenced waiting list time (WLT) for patients undergoing cataract surgery. METHODS: 70 preoperative cataract patients were interviewed by one of the authors using a questionnaire to score visual acuity, coexisting ocular pathology and disabilities, threat to independent living/employment, and perceived visual handicap for detailed, gross, and driving vision. Individuals were analysed separately according to whether it was their first or second cataract operation. RESULTS: The median WLT for first eye surgery was 9 months (n = 31) and 13 months for second eye surgery (n = 36). The WLT ranged from 2 to 25 months for first eyes and 0.25–18 months for second eyes. Where there was a perceived threat to independent living or employment the WLT was found to be significantly shorter than the median. A high overall score correlated with a shorter WLT. Surgical priority was also given to individuals with anisometropia >3 dioptres. CONCLUSION: This study has demonstrated that there are specific factors that influence clinicians when prioritising patients for cataract surgery.